PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN EKOWISATA WOLOBOBO DI DESA LANGA KECAMATAN BAJAWA KABUPATEN NGADA NUSA TENGGARA TIMUR - Gilbertha Christina Moi; Primus Gadu; Ajuar Abdullah (Program Studi S1 Pariwisata, Sekolah Tinggi Pariwisata Mataram, 2023)
One of the developments of Ngada Regency Ecotourism that is currently starting to emerge and be developed is the Wolobobo Ecotourism destination. The number of tourists who come to visit is now increasing this is due to the participation of the community, where the community is very involved and enthusiastic about working with everything it can do so that Wolobobo Ecotourism can develop well and become an advanced Ecotourism Area. The purpose of community participation for the Wolobobo Ecotourism area in Langa Village is expected to be able to develop the Ecotourism Area into the number one Ecotourism destination in Bajawa District, Ngada Regency, NTT Province with high community participation, will make this Wolobobo Ecotourism destination into a community-based tourist area. This type of research is a type of Descriptive research with a Qualitative approach, informants in this research in this research are village heads, (representatives), Pokdarwis, managers, and the community. The techniques used in this study are data collection techniques in the form of observation, interviews and documentation. Meanwhile, data analysis techniques use data reduction, data presentation, and drawing conclusions. The results of this study show that the community in Langa Village has participated in their respective ways and implemented the work program that has been made, the conclusion of this study is that the participation of the Langa village community in the development of Wolobobo Ecotourism is very high, although there are several inhibiting factors.